A multidomain lifestyle intervention to maintain optimal cognitive functioning in Dutch older adults—study design and baseline characteristics of the FINGER-NL randomized controlled trial - Deckers, Kay; Zwan, Marissa D.; Soons, Lion M.; Waterink, Lisa; Beers, Sonja; van Houdt, Sofie; Stiensma, Berrit; Kwant, Judy Z.; Wimmers, Sophie C. P. M.; Heutz, Rachel A. M.; Claassen, Jurgen A. H. R.; Oosterman, Joukje M.; et al. (Alzheimer's research & therapy, 2024)
Background Evidence on the effectiveness of multidomain lifestyle interventions to prevent cognitive decline in older people without dementia is mixed. Embedded in the World-Wide FINGERS initiative, FINGER-NL aims to investigate the effectiveness of a 2-year multidomain lifestyle intervention on cognitive functioning in older Dutch at risk individuals. Methods Multi-center, randomized, controlled, multidomain lifestyle intervention trial with a duration of 24 months. 1210 adults between 60–79 years old with presence of ≥ 2 modifiable risk factors and ≥ 1 non-modifiable risk factor for cognitive decline were recruited between January 2022 and May 2023 via the Dutch Brain Research Registry and across five study sites in the Netherlands. Participants were randomized to either a high-intensity or a low-intensity intervention group. The multidomain intervention comprises a combination of 7 lifestyle components (physical activity, cognitive training, cardiovascular risk factor management, nutritional counseling, sleep counseling, stress management, and social activities) and 1 nutritional product (Souvenaid®) that could help maintain cognitive functioning. The high-intensity intervention group receives a personalized, supervised and hybrid intervention consisting of group meetings (on-site and online) and individual sessions guided by a trained lifestyle coach, and access to a digital intervention platform that provides custom-made training materials and selected lifestyle apps. The low-intensity intervention group receives bi-monthly online lifestyle-related health advice via the digital intervention platform. Primary outcome is 2-year change on a cognitive composite score covering processing speed, executive function, and memory. Results Within 17 months, participant recruitment has been successfully completed ( N = 1210; mean age: 67.7 years (SD: 4.6); 64% female). Modifiable risk factors commonly present at baseline were physical inactivity (89%), low mental/cognitive activity (50%), low social engagement (39%), hypertension (39%) and high alcohol consumption (39%). The mean body mass index of participants was 28.3 (SD: 4.2) and the total serum cholesterol was 5.4 mmol/L (SD: 1.2). Conclusions Baseline lifestyle and clinical measurements showed successful recruitment of participants with sufficient potential for prevention. Results of FINGER-NL will provide further insight into the efficacy of a multidomain lifestyle intervention to prevent cognitive decline in older adults. Trial registration ClinicalTrials.gov (ID: NCT05256199)/2022–01-11.